PENGEMBANGAN MODUL MATA KULIAH GAMBAR TEKNIK SEBAGAI UPAYA UNTUK MENINGKATKAN PRESTASI MAHASISWA PADA JURUSAN TEKNIK MESIN D3 IST AKPRIND YOGYAKARTA - Aji Pranoto (Universitas Negeri Yogyakarta, 2019)
This research aim to: (1) know the module development process, (2) to know the feasibility and (3) find out the effectiveness of the module to interpret engineering drawings, which have been made to support learning in interpret engineering drawings subject. The method that used in this research is research and development methods. Collection data was done by using questionnaires and test questions. The techniques of data analysis was done by using descriptive analysis techniques, by analyzing quantitative data and then interpreted in a qualitative sense. The results showed that: (1) learning module development process carried out in four main stages: needs analyze, design and creating a module, testing the feasibility and effectiveness of testing modules, (2) feasibility testing shows an average percentage value 88% with